International experience of using the economic expertise in financial investigations - Oliynychuk, Oleksandra; Kuper, Mariia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
This article discusses the ways to increase the effectiveness of the domestic law enforcement system in the fight against economic crimes, which requires a comprehensive study of international experience in financial investigations, expert participation in the application of special economic knowledge, including economic expertise. The purpose of the article is to study the modern world experience of using special economic knowledge by an expert in financial investigations and to outline promising areas of its application in domestic practice. In the article was noted that economic expertise can be considered as a procedural action, where special economic knowledge is used to study accounting information and provide an opinion to law enforcement agencies and the court to make a fair decision. The use of special economic knowledge by an expert and conducting economic expertise helps to conduct financial investigations and, at the same time, requires the applying of highly professional knowledge in all areas of accounting, economic control and economic analysis, which are special, ie mostly uncharacteristic of the investigator or court. International European integration policy promotes the introduction in Ukraine of a positive experience of using special economic knowledge in the detection and investigation of criminal offenses of an economic nature. In this case financial investigations are an important tool for ensuring the economic security of the state as a whole and individual businesses, and economic expertise is one of the components in their conduct. The development of forensic services for private business entities in the domestic practice is considered promising, based on the relevant international experience. This can expand the scope of the examination with the involvement of an expert accountant and, accordingly, help strengthen their economic security.